Pengaruh Kompetisi terhadap Stabilitas Perbankan di Indonesia - Pranita Siska Utami; Ida Uliyah; Ravindra Ardiana Darmadi (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
Banking is an important sector for a country's economy, therefore maintaining banking stability is very important because if there is a problem it can have a direct impact on economic conditions in that country. One of the factors that influences growth stability is competition. This research aims to determine the effect of competition on banking stability in Indonesia. This research was carried out with data samples from 43 banks in the 2018-2021 period. The analytical tool used was Z-score value analysis, the Leaner Index with Stata 17.0 panel data regression. The research results show that competition can explain the dependent variable, namely stability of 5.20%.